Substitution of Rose Petal in Making Sponge Cake - Nisa Rahmaniyah Utami; Johan Amaril Harahap (Media Pendidikan Gizi dan Kuliner, 2022)
Roses are plants that have many benefits, vitamin content and uses, for example in the field of food products, in this field most roses are usually used for garnishing desserts only. The use of roses in the field of food products is still very little used, the author wants to make something new by using these rose petals in the product field, by making these rose petals into flour which will later be used in making sponge cake, which later in the process of making this sponge cake there is the addition of rose petal powder which the writer made with wheat flour, and the writer wants to know the results of adding rose petal powder in making this sponge cake whether it can be accepted and liked by the public.The methodology used by the author in this research is experimentationwith a completely randomized design (CRD) consisting of 3 treatments,through a series of trials to find a standard recipe for manufacturesponge cake by usingroses. The results obtained by the author after collecting and processing respondent questionnaire data (people) with 4 (four) different aspects, namely color, aroma, texture, taste in substitution of rose petals in making this sponge cake, namely, panelists are not experts with a total score of overall 3 formulas 41.4% with an average of 3.45, for the formula with the highest score in formula 2 (two) with a total score of 14 with an average of 3.5, for the next highest score in formula 1 (one) with the total score is 13.8 with an average of 3.45, and for the smallest score, namely formula 3 (three) with a total score of 13.6 with an average of 3.4. The results of this study indicate that the use of rose petal powder in making sponge cake can be said to be successful with the results of the preference test which is dominated by liking.